A short history of early Hebrew : cases, articles, alphabets and some early texts - Van Rooy, H. F. (Journal for semitics, 2011)
This article discusses some aspects of the early history of Hebrew, in the light of the view still held by many conservative or evangelical scholars that Moses wrote the Pentateuch. Important questions to be answered are what alphabet could have been used at about 1200 B.C.E., what was the state of Northwest Semitic languages at that stage and how did Hebrew evolve from the older language strata. Important indications are the developments regarding cases, articles, vowel letters and the loss of certain consonants. For the discussion a number of Ugaritic, Hebrew, Aramaic and Phoenician texts are discussed. The language of the last part of the second millennium and the language of the Pentateuch clearly come from different eras.